KOMPARASI METODE ECOMOMIC ORDER QUANTITY DAN JUST IN TIME TERHADAP EFISIENSI BIAYA PERSEDIAAN - Putri Lestari; Dedi Darwis; Damayanti Damayanti (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2019)
Solo Rambak Crackers Factory is a home industry. The production process often occurs problems with raw material supplies. If the supply of raw materials in the form of oil is stored for a long period of time and used repeatedly, the problem that occurs is that the oil will experience discoloration, odor and is not good for food that is managed with the oil. This causes the company to be faced with the amount of raw material inventory costs. The purpose of this study is to make an application to compare the calculation of raw material inventory and test which method is appropriate to be implemented in the company in terms of the cost efficiency aspects of inventory. The method used in this study is the Economic Order Quantity (EOQ) and Just In Time (JIT) methods. This raw material inventory calculation is used to minimize inventory costs. To get the maximum results and the right calculation in accordance with the formulas that are set, it requires a comparative system between computer-based EOQ and JIT methods in order to get detailed and accurate results on the calculation and comparison of the results of the value of the raw material inventory. The existence of this comparative system no longer needs to manually calculate and compare values ​​using only the system. From the results of the comparison of the two methods, in an effort to increase the efficiency of raw material inventory costs, the company can use the Just In Time method, purchases are made in small quantities and shipments are in scale, so as to reduce the occurrence of storage costs.